Effects of fundamental movement skills–based physical education on gross motor competence among children in Makassar - Sufitriyono, Sufitriyono; Fatoni, Fatoni; Yani, Ahmad; Syafruddin, Muhammad Akbar; Andi Sahrul Jahrir; Musa Muhammad Musa Hashlol (Tanjungpura Journal of Coaching Research, 2026)
Background Gross motor competence is essential for children’s physical development and participation in physical activity and sport. However, physical education (PE) in many elementary schools provides limited opportunities for structured and progressive fundamental movement skills (FMS) practice, potentially constraining the development of locomotor and ball skills. Objectives This study examined the effects of an eight-week FMS-based PE program on gross motor competence among elementary school children in Makassar, Indonesia, compared with regular PE. Methods A controlled school-based pretest–posttest study involved 60 children aged 8–11 years, allocated to an intervention group (n = 30) or control group (n = 30). The intervention group completed an FMS-based program integrated into regular PE lessons and delivered by PE teachers twice weekly for eight weeks. The program emphasized progressive locomotor and ball-skill activities, increased practice opportunities, and cue-based feedback. The control group continued its usual PE lessons. Gross motor competence was assessed using the Test of Gross Motor Development–Third Edition (TGMD-3), comprising Locomotor, Ball Skills, and Total scores. Posttest outcomes were compared using analysis of covariance, adjusting for baseline scores. Effect sizes were expressed as partial eta squared (η²p) and Cohen’s d. Results The intervention group demonstrated greater improvement in the TGMD-3 Total score (45.00 ± 5.00 to 51.50 ± 4.80) than the control group (44.60 ± 4.70 to 46.10 ± 4.90). Adjusted analyses indicated a large intervention effect on the Total score (η²p = .35; d = 1.10). Substantial effects were also observed for Locomotor (η²p = .22; d = 0.95) and Ball Skills scores (η²p = .20; d = 0.90). Conclusion Integrating structured and progressive FMS instruction into routine, teacher-delivered PE improved children’s gross motor competence. This approach represents a feasible curriculum-enrichment strategy for elementary schools in urban Indonesian settings.